Peran Media Sosial X Dalam Perkembangan Komunikasi Di Era Digital - Muhammad Adnan Faidh; Muhamad Esa Maulana; Ninda Ela Putri; Siti Indriyani Putri; Thasya Azhari Munir; April Laksana (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
Among social media users x is one of the popular platforms. The x application plays a significant role in dissemination and development that not only becomes a medium for spreading news but also becomes an ecosystem that supports evolution and adaptation. Through interaction and creativity contribute to dynamics, making application one of the major factors in development in the digital age. In this article, the writer reviewed social media users x. this study aims to identify the types of times in which they often use and to understand their context. Through qualitative approaches data is collected from the posts of social media users x and analyzed using the method of analyse analysis. Results. Research shows that social media USES a lot of information about other news items. Much about applications x:slang, viral news, online loan services (pinjol), and so forth, takes serious action from governments, communities, and parents to address this problem. Social media plays a very important role in the digital age, referring to the use of social media platforms to interact and communicate with others. There are positive effects on social media x (facilitating interaction and expanding association, there are many viral things), but it can also have a negative effect like spreading false information.